Soil Microbiome Structure and Function in Ecopiles Used to Remediate Petroleum-Contaminated Soil - Wang, M.; Garrido-Sanz, D.; Sansegundo-Lobato, P.; Redondo-Nieto, M.; Conlon, R.; Martin, M.; Mali, R.; Liu, X.; Dowling, D. N.; Rivilla, R.; Germaine, K. J. (Frontiers in Environmental Science, 2021)
The soil microbiome consists of a vast variety of microorganisms which contribute to essential ecosystem services including nutrient recycling, protecting soil structure, and pathogen suppression. Recalcitrant organic compounds present in soils contaminated with fuel oil can lead to a decrease in functional redundancy within soil microbiomes. Ecopiling is a passive bioremediation technique involving biostimulation of indigenous hydrocarbon degraders, bioaugmentation through inoculation with known petroleum-degrading consortia, and phytoremediation. The current study investigates the assemblage of soil microbial communities and pollutant-degrading potential in soil undergoing the Ecopiling process, through the amplicon marker gene and metagenomics analysis of the contaminated soil. The analysis of key community members including bacteria, fungi, and nematodes revealed a surprisingly diverse microbial community composition within the contaminated soil. The soil bacterial community was found to be dominated by Alphaproteobacteria (60–70%) with the most abundant genera such as Lysobacter, Dietzia, Pseudomonas, and Extensimonas. The fungal community consisted mainly of Ascomycota (50–70% relative abundance). Soil sequencing data allowed the identification of key enzymes involved in the biodegradation of hydrocarbons, providing a novel window into the function of individual bacterial groups in the Ecopile. Although the genus Lysobacter was identified as the most abundant bacterial genus (11–46%) in all of the contaminated soil samples, the metagenomic data were unable to confirm a role for this group in petrochemical degradation. Conversely, genera with relatively low abundance such as Dietzia (0.4–9.0%), Pusillimonas (0.7–2.3%), and Bradyrhizobium (0.8–1.8%) did possess genes involved in aliphatic or aromatic compound degradation.